Transformation of the rural economy - Otsuka, Keijiro; Zhang, Xiaobo (International Food Policy Research Institute, 2021)
The chapter examines whether contract farming confers benefits primarily to large farmers in practice and how we may be able to make smallholders significantly better off by introducing new profitable crops and livestock products. More often than not, agriculture does not provide ample employment opportunities, largely due to land constraints on production expansion. One solution is to develop nonfarm sectors so as to provide more lucrative employment opportunities, in which working members of farm households increasingly find jobs. The chapter demonstrates the critical importance of increasing nonfarm income to improve the income of rural households and examines the roles of infrastructure and human capital in raising nonfarm income.